Electrolyte-Labile Increase of Oxygen Affinity during In Vivo Aging of Hemoglobin - Edwards, Miles J. (1967)
Normal human erythrocytes were separated according to in vivo age by ultracentrifugation. The “young” and “old” erythrocytes had mean cell ages of approximately 40 and 79 days, respectively. “Young” erythrocytes had a lower oxygen affinity and a higher heme-heme interaction than did “old” erythrocytes. This indicates an impairment of the oxygen-carrying function of erythrocyte hemoglobin with age. “Young” and “old” erythrocytes were hemolyzed yielding “young” and “old” hemoglobins. “Young” hemoglobin had a comparably lower oxygen affinity than did “old” hemoglobin when the hemolysates were dialyzed against electrolyte-free water. Exposure to sodium chloride completely obliterated this difference between the oxygen affinities and buffer values of “young” and “old” free hemoglobin. Similar exposure to potassium chloride resulted in partial obliteration of the difference between the oxygen affinities of “young” and “old” hemoglobin. Subsequent removal of sodium chloride by dialysis did not restore the pre-electrolyte differences between the oxygen affinities of “young” and “old” hemoglobin. This evidence indicates that in vivo aging is accompanied by a conformational change of the hemoglobin molecule, which is probably due to an alteration of electrostatic interactions involving the hemoglobin molecule and which is retained after hemolysis and dialysis against water but is obliterated by addition of electrolyte. It is not possible, however, to decide from the available evidence whether this molecular change occurs independently or as a result of influences by other substances, such as 2,3-diphosphoglycerate, which also change during in vivo aging of the erythrocyte.